Regulation and operating costs of electric underfloor heaters - Sabiniak, Henryk; Wiśnik, Karolina (Instal, 2022)
Regulation of the amount and time of electricity consumption from the space heating network is the most important (critical) moment of installation design. This is related to subsequent operation, safety and costs. At the same time, it provides speed and comfort in maintaining temperature conditions in the room with minimizing the cost of using this type of heating.
Keywords: heating surface; cheaper electricity; temperature; tariff group; regulation